Effect of seed treatment on seed borne fungi of rice - Naher, L; Ali, MA; Sheheli, S (Progressive Agriculture, 2016)
Farmers of our country are not aware about seed treatment for controlling seed borne fungi. Seeds of 3 rice varieties viz. BR11, BRRI dhan30 and BRRI dhan33 were collected from farmers houses of Gopalpur, Tangail. Three seed treating fungicides viz. vitavax 200 vitavax 200 (0.25%), thiovit (0.25%) and cupravit (0.25%) were used. Collected seed samples were tested by dry inspection and blotter method. The highest and the lowest germination were recorded in seed samples of BRRI dhan30 (90%) and BRRI dhan33 (75%). After seed treatment the highest and the lowest germination were recorded in seed samples of BRRIdhan30, BRRI dhan33 (100) treated by vitavax 200 (0.25%) and BR11 (80%) in control. Seed health test by blotter method revealed seed borne fungi belonging to six genera viz. Bipolarisoryzae (2.5 to 8.53%), Alternariapadwickii (5.3 to 13.35%), Fusariummoniliforme (11.66 to 21.67%), Fusariumoxysporum (1.25 to 4.35%), Curvularialunata (1.95 to 7.5%) and Aspergillusspp (1.75 to 6.54%) were encountered. Bur after seed treatment remarkable improvement viz. Bipolarisoryzae (0.15 to 3.75%), Alternariapadwickii (0.0 to 3.0%), Fusariummoniliforme (2.16 to 5.83%), Fusariumoxysporum (0.0 to 3.0%), Curvulariaunata (0.0 to 2.56%) and Aspergillusspp (0.0 to 1.5%) were encountered. Vitavax 200 was found most effective against the seed borne pathogens of rice. Nowadays, many botanical extracts such as neem, nishinda, garlic, alamonda and biological agent such as Trichoderma also using as seed treating agent and resulted significant higher germination and plant stand, less disease incidence and higher yield of different crops. So, the farmers should treat their seed before sowing in their field and through this technique they will be more benefited. Progressive Agriculture 27 (1): 48-56, 2016